Sex Education for Young Children in the Islamic Perspective - Muryani; Lina Revilla Malik; Ismail Martono (Bulletin of Pedagogical Research, 2025)
This study aims to examine the development strategies of a self-reliant village through the Village-Owned Enterprises (BUMDes) and to review their alignment with Islamic economic principles in Tepian Langsat Village, Bengalon District, East Kutai Regency. The research method used is qualitative with a descriptive approach. Data collection techniques include interviews, observation, and documentation. The results show that BUMDes Tepian Bina Bersama operates business units such as microfinance, basic goods distribution, and social programs that directly impact community welfare and increase the Village Original Income (PADesa). The development strategies are carried out in a participatory, transparent, and locally based manner, involving both the village government and the local community. From the perspective of Islamic economics, these strategies reflect principles of justice, consultation (shūrā), transparency, and public benefit (maṣlaḥah). However, several challenges remain, including limited understanding of Islamic commercial law (muʿāmalah) among managers, the absence of fully sharia-compliant financing models, and a lack of sharia-based managerial training. Improvement efforts are being made through human resource development, transparent reporting, and continuous community engagement.